ASOSIASI KOMPETENSI TENTANG PEDOMAN GIZI SEIMBANG DENGAN STATUS INDEKS MASSA TUBUH REMAJA PUTRI DI PONDOK PESANTREN AL-ISHLAH BULUSAN KOTA SEMARANG - Fasella Dizka Febrinsa; Laksmi Widajanti; Siti Fatimah Pradigdo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Initial studies in Boarding School Al-Islah Bulusan Semarang City, as much as 50% of the nutritional status of female teenagers experienced more nutrition. Today's teens have unhealthy eating patterns. Implementation competencies include knowledge, attitudes and skills about the selection of food in accordance with the standards of Indonesia Balanced Nutrition Guidelines are needed to improve nutritional awareness. The purpose of this study to determine the association of Indonesian Balanced Nutrition Guidelines competence with a body mass index status of female teenagers. The design studies with cross-sectional survey. The sampling technique was by purposive sampling amounted to 44 female teenagers. Data were collected through interviews and analyzed using Rank Spearman Rank test. The results showed that the status of the body mass index in young women is almost entirely better nutritional status (95.5%), lack of energy consumption (86.4%), lack of protein consumption (95.5%), and competence level about Balanced Nutrition Guidelines were good (84.1,%). In general, if the level of competence is seen from the competence of knowledge about Balanced Nutrition Guidelines were good (56.8%),competence level of attitudes about Balanced Nutrition Guidelines for attitude positive (52.3%), and competence level of skills about Balanced Nutrition Guidelines were good (40.1%). Based on Rank Spearman test there is a relationship of competence (knowledge,attitudes, skills) with a body mass index status (p-value = 0.017 and the correlation coefficient (ρ) = -0.359). The board suggested that boarding schools improve food management and curb the purchase of food at boarding corresponding Balanced Nutrition Guidelines.